The Effect of Perceived ROI on Perceived Value and Adoption Intention - Rizki Pratama Johanis Paransa; Rr. Chusnu Syarifa Diah Kusuma; Fajar Wahyu Nugroho; Kurnia Wulandari (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study aims to examine the role of perceived return on investment (ROI) in shaping perceived value and its impact on adoption intention toward digital branding among small and medium-sized enterprises (SMEs). A quantitative approach with an explanatory research design was employed, involving 100 SME owners in the Special Region of Yogyakarta, Indonesia. Data were collected through structured questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that perceived ROI has a positive and significant effect on perceived value with a t-statistic of 4.562 and a p-value of 0.000 (<0.05) and the path coefficient is 0.513, suggesting that SMEs evaluate digital branding based on the economic benefits gained relative to the costs incurred. Furthermore, perceived value has a positive and significant effect on adoption intention with a t-statistic of 8.781 and a p-value of 0.000 (<0.05) and the path coefficient is 0.625, indicating that perceived value is a determinant in technology adoption decisions. Theoretically, this study provides insights into the importance of value-based evaluation in the context of digital branding adoption among SMEs. Practically, the results suggest that improving SMEs’ understanding of digital branding performance, particularly in terms of ROI, can enhance perceived value and encourage broader adoption of digital branding strategies.